Upaya Antisipatif terhadap Paham dan Perilaku Radikalisme Agama di Lingkungan Sekolah (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Religious radicalism in the school environment has become an increasingly important issue due to its potential to influence students’ mindsets, attitudes, and behaviors. This study aims to examine anticipatory efforts to prevent the development of radical religious ideologies and behaviors within schools. The research employs a qualitative approach with a descriptive design, utilizing data collection techniques such as interviews, observations, and document analysis. The findings indicate that anticipatory efforts can be implemented through strengthening character education, integrating values of religious moderation into the curriculum, enhancing the role of teachers as agents of guidance, and fostering active involvement of parents and the community. Furthermore, creating an inclusive, tolerant, and dialogical school environment is a crucial factor in countering radicalism. In conclusion, preventing religious radicalism in schools requires a holistic approach involving all elements of education in a sustainable manner. This study is expected to serve as a reference for educational institutions in formulating effective preventive strategies against religious radicalism.